Chapter Brevi considerazioni sul disegno leonardiano del territorio tra visione olistica e restituzione selettiva dei fenomeni - Cantile, Andrea (Territori, 2023)
Leonardo's conception of drawing and painting as a "science", intended as a means to know material reality, in its application to the cartographic field highlights the Master's adoption of different criteria for selecting and arranging information content in maps. Considering some significant cases, the text highlights Leonardo's main contributions to cartography and proposes to consider these discrepancies as the results of an investigative process, in which the permanence and mutability of objects and territorial phenomena are evaluated in close relation with the project.